Analysis of the Effect of Work Motivation on Nurse Performance at PUSKESMAS - Ali Zaenal Abidin (Program Studi Pendidikan Ekonomi, IKIP Budi Utomo Malang, 2020)
The purpose of this study was to determine the phenomenon and obtain empirical evidence, as well as conclusions about the effect of work motivation on the performance of the nurses at Community Health Center. This research uses quantitative descriptive methods. The type of data used is primary data. The sample used was 125 nurses. Data processed using SPSS 19 program. The results showed that (1) Simple Linear Regression Test Results produced a regression equation: Y = 22,292 + 0605 X. (2) The results of the correlation coefficient test of 0.522 included in the medium category. This means that work motivation has a moderate relationship with performance variables. (3) Determination Coefficient Test Results are 0.273. This means that work motivation variables contribute 27.3% to the performance variable. The remaining 72.7% is influenced by other factors not examined. (4) From the t test table it can be seen that t arithmetic> t table, which is 6,792> 0,676, meaning that the work motivation variable has a positive and significant effect on the performance of the nurses at Community Health Center